Resilience and positive coping style affect the relationship between maladaptive perfectionism and academic procrastination among Chinese undergraduate nursing students - Huang, Haitao; Ding, Yueming; Zhang, Yiming; Peng, Qianwen; Liang, Yipei; Wan, Xiao; Chen, Chaoran (Frontiers in Psychology, 2022)
Background Previous studies have not investigated the role of resilience and coping style on the association between maladaptive perfectionism and academic procrastination among nursing undergraduates. However, how to mobilize the learning enthusiasm of nursing students and reduce the incidence of academic procrastination is an important factor to reduce nursing loss and improve nursing quality. Objectives To investigate the influence of maladaptive perfectionism, resilience and coping style on academic procrastination among Chinese undergraduate nursing students. Methods A cross-sectional study was conducted. A convenience sampling method was used to select 665 nursing undergraduates from March to May 2022 in China. Maladaptive perfectionism, coping style, resilience, and academic procrastination were measured using questionnaires. The descriptive analysis, Pearson’s correlation analysis and the Hayes’ PROCESS Macro in SPSS 25.0 were used to test the model. Results The results showed that nursing undergraduates’ maladaptive perfectionism, resilience, positive coping style and academic procrastination were significantly correlated between every two variables, with coefficients ranging between −0.290 and 0.584. In addition, resilience played a partial mediating role in maladaptive perfectionism and academic procrastination, accounting for 15.70% of the total effect; in the meantime, this process was moderated by positive coping style. Conclusion Maladaptive perfectionism positively predicted nursing undergraduates’ academic procrastination; as a mediating mechanism with moderating, resilience and positive coping style further explained how maladaptive perfectionism promoted the academic procrastination of nursing undergraduates. Understanding this mechanism is of great significance for nursing educators to reduce the risk of academic procrastination in nursing undergraduates.